Validation of a Questionnaire on the Factors of University Failure in Morocco (Medico Legal Update, 2021)
Objective: The objective of this researchis to develop and validate a solid and reasonablescale to measurethe failure of students in Morocco.Material and Method: This is a cross-sectional study, which took place between November 2019 and March2020. The internalreliability of the questionnaire waschecked by calculating the Cronbach’s CoefficientIndex, and a factor analysis was performed.Results: The population of ourstudyis 184 students of three masters in teaching and education, UniversityIbn Tofail of Kenitra-Morocco. The averageage at the time of enrollment in the first-year master’s degreeis26.59±5.65 years. Regarding gender, wenoted that males represent a percentage of 71.2% (n=131), whilefemales represent 28.8% (n=53) with a sex ratio (m/f) of 2.4 (p